Silica/poly(vinylidene fluoride) porous composite membranes for lithium-ion battery separators - Costa, C. M. (2018)
Separator membranes based on silica/poly(vinylidene fluoride) composites were prepared by a non-solvent induced phase separation (NIPS) process with different air exposure times before immersion in a water coagulation bath and for the same filler content of 20 wt%. Mesoporous silica spheres (SS) of ~ 400 nm average diameter were synthetized by sol-gel method and dispersed into the polymer matrix. It was demonstrated that the morphology, degree of porosity, uptake value and electrical properties of the composite membranes were influenced by the time of exposure to air and the presence of SS. The membranes were assembled in Li/C-LiFePO4half-cells and the best cycling performance was obtained for the composite membrane after 1 min exposure to air. This membrane shows an ionic conductivity of 0.9 mS cm−1. Moreover, at a very high rate of 2 C and after 50 cycles, the discharge capacity value, a capacity retention and a capacity fade are 95 mA h g−1, 79% and 4%, respectively. Thus, it was concluded that this novel separator membrane is suitable for lithium-ion battery applications.